The Neck, (Haystack) from the eastern end (1920)
Taken from the Eastern end with the new Methodist Church and LOA hall in the background. This collection contains copies made in 1998 of original photographs gathered by the Haystack Reunion Committee for publication in their booklet Haystack Reflections (1997).